2014
DOI: 10.1172/jci69413
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient sensing by the mitochondrial transcription machinery dictates oxidative phosphorylation

Abstract: Sirtuin 3 (SIRT3), an important regulator of energy metabolism and lipid oxidation, is induced in fasted liver mitochondria and implicated in metabolic syndrome. In fasted liver, SIRT3-mediated increases in substrate flux depend on oxidative phosphorylation (OXPHOS), but precisely how OXPHOS meets the challenge of increased substrate oxidation in fasted liver remains unclear. Here, we show that liver mitochondria in fasting mice adapt to the demand of increased substrate oxidation by increasing their OXPHOS ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 57 publications
2
40
0
Order By: Relevance
“…Gene expression of mitochondrial-encoded NADH dehydrogenase 1 ( mt-Nd1 ) relative to nuclear 18S rRNA was used to determine mitochondrial DNA copy number as previously described. 41 …”
Section: Methodsmentioning
confidence: 99%
“…Gene expression of mitochondrial-encoded NADH dehydrogenase 1 ( mt-Nd1 ) relative to nuclear 18S rRNA was used to determine mitochondrial DNA copy number as previously described. 41 …”
Section: Methodsmentioning
confidence: 99%
“…In mitochondria, SIRT3 serves as an important regulator of energy metabolism (Liu et al, 2014) and is highly expressed in metabolically active tissues such as brown adipose tissue, muscle, liver, kidney, heart, and brain. Particularly in the skeletal muscle, SIRT3 expression is sensitive to the diet (Palacios et al, 2009).…”
Section: What Causes the Nad Decline Observed During The Aging Process?mentioning
confidence: 99%
“…Our findings are in agreement with previous evidences highlighting increased OXPHOS activity as an important physiological adaptation in the liver during starvation. Similarly as in S. aurata , starvation increases cytochrome c oxidase activity and the transcription of OXPHOS genes in the liver of mice [26, 27], and enhances the activity of cytochrome c oxidase in human fibroblasts [28]. Moreover, a microarray analysis conducted on liver samples of mice indicated that 75% of diet restriction results in a modest but significant increased expression of an important number of OXPHOS genes [51].…”
Section: Discussionmentioning
confidence: 99%
“…Starvation increases the rate of oxygen consumption at about 20% in the rat liver [25], and enhances cytochrome c oxidase activity in the liver of mice [26]. Starvation increases OXPHOS activity in the liver of mice by stimulating the transcription and efficiency of OXPHOS genes in a process triggered by glucagon/cAMP signalling [27]. Similarly, starvation impairs the glycolytic flux, reduces the ATP/AMP ratio and significantly enhances the activity of cytochrome c oxidase in human fibroblasts [28].…”
Section: Introductionmentioning
confidence: 99%